Impact of nonuniform reactant flow rate on the performance of proton exchange membrane fuel cell stacks. Issue 11 (1st September 2020) - Pan, Mingzhang; Meng, Xianpan; Li, Chao; Liao, Jinyang; Pan, Chengjie
ABSTRACT: In this study, a proton exchange membrane (PEM) fuel cell stack composed of five cells in series is numerically investigated to study the impact of the nonuniform reactant flow rate on the performance of the stack. A comparison of the water concentration, temperature, reaction heat source, and current density of change rule of two groups of fuel cell stacks with uniform and nonuniform reactant flow rate reveals the performance degradation mechanism caused by nonuniform reactant flow. The results indicate that while operating under low-voltage conditions, the nonuniform reactant flow rate will cause the accumulation of excess liquid water near the PEM that is near the cathode exhaust outlet, and the local area reacts strongly on the catalyst, whereas the local area reacts slowly. When the average voltage of the stack is 0.55 V, the current density under the nonuniform reactant flow rate condition is 12.9% lower than that of the uniform reactant flow rate condition. In the case of uniform and nonuniform reactant flow rate at low current densities, the performance difference is not evident, but it is expected to be pronounced with the increase in current density. The simulation results are compared with the experimental data reported in the literature through a polarization curve, and they turn out to be well correlated with the experimental results.